Entrepreneurship in community-based tourism in Sri Lanka - Kaluarachchige, Indika Priyantha; Shukri Ab Yajid, Mohd; Khatibi, Ali; Azam, S.M. Ferdous (Turyzm/Tourism, 2021)
This study is focused on entrepreneurship in community-based tourism (CBT) in Sri Lanka. It examines the effect of entrepreneurial competences and orientation towards the performance of homestays although the majority are not successful. Recent research has revealed that homestay tourism is not effective, nonetheless it has been identified as the sector for the development for entrepreneurs and can make a considerable contribution to the Sri Lankan economy. The purpose of this study is to enhance CBT by showing how to develop productive entrepreneurs in this sector. Resource based view (RBV) theory is the basis – 645 registered homestay units operate as a CBT practice and the study sample was 252 entrepreneurs. Structural equation modelling (SEM) was used to analyze the data. From the findings of the study, both entrepreneurial competences and orientation significantly affect entrepreneur performance in CBT. This study will help expand CBT for successful entrepreneurs emerging from the tourism sector.